POSSIBILITIES OF EVALUATION OF THE POST-AMPUTATION WALKING USING THE KINOVEA SOFTWARE - Cotrobaş-Dascălu, Vlad-Theodor; Stoica, Marius; Dreve, Adina Andreea (The International Scientific Conference eLearning and Software for Education, 2021)
The amputation is represented by the deliberate surgical removal of a limb, limb segment, or body part. From an etiological point of view, the amputations are caused by chronic vascular diseases, diabetes, tumors and trauma. At the lower limbs, the amputation can be performed at the following levels: finger amputation, transmetatarsal amputation, Lisfranc amputation, Chopart amputation, Syme amputation, transtibial amputation, rotationplasty, knee disarticulation, transfemoral amputation, hip disarticulation and hemipelvectomy. The level of the amputation is determined by factors such as: at the amputations caused by a trauma, the viable tissue determines the level, and in the case of vascular diseases with infection, the level is determined by the unaffected vascular area. The transfemoral amputation is performed through the femoral and thigh muscles and covers almost 85% of all amputations. At patient with transfemoral amputation, there is only a 25% success from the prosthesis use. From a therapeutic point of view, the patient with amputation is approached by an interdisciplinary team that can be consisted of: doctor, nurse, psychologist, physiotherapist, orthopedic technician, occupational therapist and social worker. This study involves conducting a case study to analyze the walking in the context of a transfemoral amputation. The support time on the ground, on the foot with which the subject walks with the prosthesis and the distance of the step of the prosthetic segment was evaluated. Kinovea is a free 2D motion analysis program that can be used to measure kinematic parameters and allows the user to control time parameters and evaluate angles and distances frame by frame. It allows the user to control time parameters and measure angles and distances frame by frame.